Characterization of the Sendai virus V protein with an anti-peptide antiserum - Curran, Joseph (Virology, 1991)
The Sendai virus V protein, which is a fusion of the P and V ORFs of the P gene, was characterized with antisera to a portion of the V ORF and compared to the P protein. The only property found in common with P is that V is also highly phosphorylated, and this is so even when these proteins are expressed independently of the other viral proteins. Otherwise, V was not found in virions, was not strongly associated with viral nucleocapsids like P, and anti-V had no effect on viral RNA synthesis in vitro under conditions where anti-P was highly inhibitory. The available evidence suggests that V may playa role in RNA synthesis, but it is not an essential one like that of the P protein.